Simultaneous Alveolar Cleft Closure and Dental Midline Correction With Curvilinear Intraoral Distraction - GÖZNELİ, RİFAT (ALLIANCE COMMUNICATIONS GROUP DIVISION ALLEN PRESS, 2014)
This article describes a new method that enables vector control during alveolar distraction osteogenesis in the treatment of a cleft palate patient. The patient presented with unilateral complete cleft lip and palate, and the alveolar part of the defect was covered by a mobile buccal flap. The distraction was performed by sliding the surgically released tooth segment with the help of an intraoral distractor over 1.5-mm stainless steel archwires held by metal crowns. This vector-controlled method enabled new bone and attached gingiva formation in harmony with the proper alveolar shape.
Keywords: archwise; distraction osteogenesis; vector control; INTERDENTAL DISTRACTION; OSTEOGENESIS; TRANSPORT; MANAGEMENT; DEVICE